2022
DOI: 10.3389/fpsyg.2022.1015190
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of influencing factors of subjective career unsuccessfulness of vocational college graduates from the Department of Navigation in China

Abstract: The marine talent cultivation and output in higher vocational colleges is an important support to build a strong maritime country and ensure the steady development of the shipping business industry. Vocational colleges should ensure effective career preparation and career guidance education for their students, and train them to acquire the professional abilities to work and adapt effectively and quickly in the future. Some studies show that many crew members experience a decline in job satisfaction, a low sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…First, written consent was obtained from the respondents, and the interviews were recorded using notes and audio recordings, ensuring that the information obtained was accurate. Immediately after the interviews, the respondents’ comments and opinions were sorted, and the responses that were consistent with the research topic were screened through a review form to establish authenticity and dependability ( Wang et al, 2022 ). Furthermore, while reviewing the data in cooperation with a supervising professor to clarify the concepts and ensure the correctness and reliability of the analysis, three colleagues majoring in art and a part-time teacher from a company were invited to assist in data review and feedback because triangulation can avoid biases and distortions in data analysis caused by personal emotions or opinions.…”
Section: Methodsmentioning
confidence: 99%
“…First, written consent was obtained from the respondents, and the interviews were recorded using notes and audio recordings, ensuring that the information obtained was accurate. Immediately after the interviews, the respondents’ comments and opinions were sorted, and the responses that were consistent with the research topic were screened through a review form to establish authenticity and dependability ( Wang et al, 2022 ). Furthermore, while reviewing the data in cooperation with a supervising professor to clarify the concepts and ensure the correctness and reliability of the analysis, three colleagues majoring in art and a part-time teacher from a company were invited to assist in data review and feedback because triangulation can avoid biases and distortions in data analysis caused by personal emotions or opinions.…”
Section: Methodsmentioning
confidence: 99%
“…Personal factors refer to personal learning experience, work experience, age, marital status, professional title, etc. (Eccles & Wigfield , 2020;Wang et al, 2022). Environmental factors may include the working environment and social environment on board the ship, such as the communication atmosphere between colleagues, the cooperation situation, and the impact of the rapid development of an external situation on the crew (Wang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…(Eccles & Wigfield , 2020;Wang et al, 2022). Environmental factors may include the working environment and social environment on board the ship, such as the communication atmosphere between colleagues, the cooperation situation, and the impact of the rapid development of an external situation on the crew (Wang et al, 2022). The working conditions and quality of the crew also largely reflect their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Research has demonstrated that students with higher levels of WB tend to exhibit better academic achievements, higher motivation, and improved overall adjustment [10]. Particularly in vocational education, where students are preparing for distinct careers, prosocial behavior holds implications for their future professional interactions and community contributions [11,12]. Consequently, understanding the factors contributing to WB, such as prosocial behavior, is paramount for educational psychologists and practitioners striving to create supportive learning environments and enhance students' educational experiences.…”
Section: Introductionmentioning
confidence: 99%